The Effect of Training, Organizational Flexibility, and Proactive Personality on Learning Agility to Enhance Employee Agility - Nurmiyati Nurmiyati; Tjutju Yuniarsih; Disman Disman; Ade Sobandi; Budi Harto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In increasingly dynamic and technology-driven environments, healthcare professionals are required to adapt rapidly, making employee agility a critical capability. This study is to analyze the influence of employee training, organizational flexibility, and proactive personality on learning agility, as well as the impact of learning agility on employee agility. This study employs an explanatory quantitative approach, with data collected from 177 physicians in Semarang Regency using purposive sampling techniques. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that employee training and organizational flexibility have significant positive effects on learning agility, and that learning agility, in turn, significantly enhances employee agility. However, proactive personality does not exhibit a significant effect on learning agility. These findings suggest that organizational factors and structured training play a more dominant role than individual characteristics in fostering adaptive capabilities among healthcare professionals. In conclusion, strengthening training programs and enhancing organizational flexibility are essential strategies for improving employee agility, particularly within highly structured and rapidly evolving healthcare environments.